Pendampilangan Identifikasi Kesiapan Fisik Dan Status Hemodinamik Calon Atlet Sepakbola U-16, U-18, Dan U-20 - Andi Ummul Hairi; Mariyal Qibtiyah; Irfan Yunus; Muhammad Naufal Ramadhansyah; Wirya Dipo Utama (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to identify the physical readiness and hemodynamic status of prospective U-16, U-18, and U-20 soccer athletes in the regional selection phase based on sports science. Measurements include aerobic capacity (VO₂max) through a bleep test, as well as blood pressure and body temperature checks. Results: This community service activity successfully mapped the physical and hemodynamic conditions of prospective regional soccer athletes. The majority of athletes had a good aerobic capacity category (U-16: 46.70; U-20: 49.37 ml/kg/min), but more than 50% of them experienced pre-hypertension conditions. Conclusion: The majority of athletes had excellent physical readiness, but the high rate of pre-hypertension requires regular cardiovascular monitoring based on sport science